2018
DOI: 10.1016/j.tate.2017.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Teachers as health promoters: Factors that influence early career teachers to engage with health and wellbeing education

Abstract: Factors that affect novice teachers' willingness to engage with health and wellbeing education are explored. An online questionnaire was sent to novice teachers in England (n=114) who had received pre-service training in health and wellbeing. Semi-structured INFLUENCES ON NOVICE TEACHERS AS HEALTH PROMOTERS 2 interviews were conducted (n=14) to support the questionnaire findings. Pre-service training appears to have some impact on new teachers. However, school ethos, attitudes of senior leadership, the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 45 publications
(77 reference statements)
0
27
0
3
Order By: Relevance
“…Firstly, pre-service training of teachers on MHM with knowledge assessment at regular intervals is a crucial step in this regard since teachers are viewed as health promoters [195,207]. Teachers' knowledge assessment can be a part of the regular school education surveys [13].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, pre-service training of teachers on MHM with knowledge assessment at regular intervals is a crucial step in this regard since teachers are viewed as health promoters [195,207]. Teachers' knowledge assessment can be a part of the regular school education surveys [13].…”
Section: Discussionmentioning
confidence: 99%
“…[68][69][70] Working for prevention and bringing health information to students represents an intrinsic ethical duty for any scholastic institution, so that teachers -who are already recognized as "promoters of culture" -should become also "health promoters" and "emotional trainers" of their students. 71 Health education should inform the ordinary teaching activities, becoming part of the daily work of school staff, who have the responsibility to guide students towards the adoption of healthy lifestyles, developing all their cognitive, affective, spiritual and social aspects, especially in a context characterized by an increasing absence of parental support at home. [72][73][74] Indeed, effective school-based preventive approaches are those that raise students' motivation towards healthy habits and foster their critical thinking about harmful consequences of the most common risky behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the reasons of teachers' neglection of health-preserving competence development. Byrne et al (2018) studied the factors that influenced early career teachers' engagement with health and wellbeing education. He concluded that pre-service teachers were not enough taught the range of health preserving educational technologies that causes the misunderstanding of primary teachers' role and physical training teachers' role in the development of the health-preserving competence in children.…”
Section: Intrоductionmentioning
confidence: 99%